Bleeding Assessment Tools: Limits and Advantages for the Diagnosis and Prognosis of Inherited Bleeding Disorders - Tosetto, Alberto (Seminars in Thrombosis and Hemostasis, 2016)
Bleeding assessment tools were first developed essentially as research tools, for the quantification of bleeding symptoms and the study of phenotype/genotype correlations. Interestingly, these tools have been proven useful also for clinicians diagnosing and treating bleeding disorders. The main advantage of these tools is the standardization of the diagnostic process, allowing the introduction of criteria with known specificity and sensitivity for the diagnosis of the most common mild bleeding disorders, particularly von Willebrand disease. This is important also for a rational approach to the laboratory diagnosis because for many mild bleeding disorders, a complex laboratory workup is required. Bleeding assessment tools should always be complemented by ancillary coagulation screening tests to exclude the presence of a bleeding disorder, however. Finally, bleeding severity assessed by such tools has been shown to correlate with the long-term probability of bleeding. Therefore, the bleeding assessment could become an important marker of disease severity.
Keywords: bleeding disorders; von Willebrand disease; diagnosis; prognosis; questionnaires